2012
DOI: 10.1111/j.1399-6576.2012.02717.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive fluid balance is associated with reduced survival in critically ill patients with cancer

Abstract: A cumulative positive fluid balance higher than 1100 ml/24 h was independently associated with mortality in patients with cancer. These findings highlight the importance of improving the evaluation of these patients' volemic state and indicate that defined goals should be used to guide fluid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 25 publications
2
28
0
2
Order By: Relevance
“…Although the initial resuscitation period after trauma has been extensively studied and has shown that administration of large volumes has detrimental effects on mortality and development of complications including coagulopathy and abdominal compartment syndrome [3,[11][12][13][20][21][22][23], very little is known about the effect of the FB status over the course of the surgical ICU stay. In our study, the percentage of trauma patients was equally divided between the FB (−) and FB (+) groups, and the aforementioned outcomes related to mortality and complications may apply to this subgroup of patients, too.…”
Section: Discussionmentioning
confidence: 99%
“…Although the initial resuscitation period after trauma has been extensively studied and has shown that administration of large volumes has detrimental effects on mortality and development of complications including coagulopathy and abdominal compartment syndrome [3,[11][12][13][20][21][22][23], very little is known about the effect of the FB status over the course of the surgical ICU stay. In our study, the percentage of trauma patients was equally divided between the FB (−) and FB (+) groups, and the aforementioned outcomes related to mortality and complications may apply to this subgroup of patients, too.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with subarachnoid hemorrhage and positive fluid balance were more likely to prolonged hospital LOS (24). In cancer patients, a cumulative positive fluid balance was independently associated with morality (25). Another study found that accumulative fluid balance from the second and third ICU days and total ICU stay fluid balance were positively associated with hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In critically ill septic and non-septic patients, the cumulative positive fluid balance has been associated with a worse outcome [29-31,34,36,37], and the administration of catecholamines, particularly at higher doses, was associated with derangements in regional blood flow [7,8], adverse side effects [33,35] and increased likelihood of death [15,32,35]. In our experimental model such effects were not observed or observable.…”
Section: Discussionmentioning
confidence: 99%